DEVELOPMENT OF CREATIVE ABILITIES OF PRESCHOOL CHILDREN (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
Activities to develop the creative abilities of preschool children through games play an important role in the formation of a child's personality. At a young age, it is recommended to pay special attention to comprehensive development, that is, to the development of literary, artistic and musical abilities of preschool children.